Sorption and desorption of phenanthrene on biodegradable poly(butylene adipate co-terephtalate) microplastics - Zuo, Lin-Zi; Li, Heng-Xiang; Lin, Lang; Sun, Yu-Xin; Diao, Zeng-Hui; Liu, Shan; Zhang, Zong-Yao; Xu, Xiang-Rong (Chemosphere (Oxford), 2019)
Biodegradable plastics, as alternatives to conventional plastics, are increasingly used, but their interactions with organic pollutants are still unknown. In this study, the sorption and desorption behaviors on a type of biodegradable plastic−poly(butylene adipate co-terephtalate) (PBAT) were investigated, and at the same time two types of conventional plastics−polyethylene (PEc and PEv) and polystyrene (PS) were used for comparison. Phenanthrene (PHEN) was chosen as one of representative organic pollutants. Results indicated that the sorption and desorption capacities of PBAT were not only higher than those of the other types of microplastics, but also higher than those of carbonaceous geosorbents. The surface area normalized results illustrated that sorption and desorption of the microplastics were positively correlated with their abundance of rubbery subfraction. The sorption kinetic results showed that the sorption rates of PBAT and PEc were higher than PEv and PS. The effects of water chemistry factors including salinity, dissolved organic matter and Cu2+ ion on the sorption process displayed the same trend, but the degrees of influence on the four microplastics differed. The degrees of influence were mainly dependent on the abundance of rubbery subfraction for microplastics. These findings indicate that the biodegradable poly(butylene adipate co-terephtalate) microplastics are actually stronger vectors than the conventional microplastics, and crystallization characteristics of the microplastics have great influences on the vector effect. [Display omitted] •Biodegradable microplastics sorbed/desorbed more PHEN than conventional ones.•Sorption/desorption capacities depended on the content of rubbery subfraction.•Plastic additives didn't alter the microplastics adsorption process.•High salinity and low DOM strengthen the sorption of PHEN onto microplastics.